Leaf-litter decomposition of the mangrove species Avicennia schaueriana, Laguncularia racemosa and Rhizophora mangle - Lima, Rene G. [UNESP]; Colpo, Karine D. (Cambridge University Press, 2014)
This study evaluated the decomposition process of leaf litter from the main Brazilian mangrove species Avicennia schaueriana, Laguncularia racemosa and Rhizophora mangle. Senescent leaves were collected, dried and placed in nylon bags with different mesh sizes (fine: 2x2mm and coarse: 8x8mm). The bags were distributed over the sediment, and replicates of each species and mesh size were collected periodically over 4months. In the laboratory, the dry weight of the samples was measured, and the decomposition coefficient (k) for each species and mesh size was obtained over time. All species showed a rapid decomposition rate at the beginning of the experiment, followed by a slower but steady rate of decomposition over time. The rate of leaf litter decomposition was highest in A. schaueriana, intermediate in L. racemosa and lowest in R. mangle. The difference was mainly linked to the activity and abundance of detritivores, together with the different litter quality of the species, which determined their palatability and probably influenced the decomposition process.
Keywords: litter mesh bag; mangrove; Brazil